Heteroatom substituted and decorated graphene: preparation and applications. Issue 48 (14th October 2015) - Chen, Nan; Huang, Xianke; Qu, Liangti
Abstract : The electronic structure and surface chemistry of graphene can be tuned subtly by doping with heteroatoms, which induces unique applications. Abstract : Graphenes have attracted increasing attention in a variety of scientific fields. By modification with foreign elements such as boron, sulfur, and fluorine, their unique electronic and spin structures can be effectively tuned and the substituted or decorated graphenes as promising materials have been successfully employed in electrical, optical, and catalytic fields. In this review, we summarize the recent advances of these newly derived heteroatom substituted or decorated graphenes with an emphasis on the preparation methods, applications and the mechanisms of action. We are hopeful for future developments of heteroatom substituted or decorated graphenes in precisely controlled substitution methods, and finding wide applications of heteroatom substituted or decorated graphenes in many different fields.